THE EFFECT OF MARKETING STRATEGIES ON INCREASING CREDIT SALES VOLUME AT KOPERASI CAHAYA ARTHA MAKMUR MANDIRI IN PURI NIRWANA CIKARANG (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Cooperatives, as a pillar of community economic development, often face challenges in sustaining credit sales volume due to suboptimal marketing strategy implementation, as observed at Koperasi Cahaya Artha Makmur Mandiri in Puri Nirwana Cikarang, which experienced profit fluctuations during 2023–2025. This study aims to examine the influence of marketing strategy on credit sales volume, drawing on the marketing mix theory by Kotler and Keller and the digital marketing concept by Chaffey and Ellis-Chadwick. A quantitative associative approach was applied using saturated sampling involving 56 cooperative members as respondents. Data were collected through a 30-item Likert-scale questionnaire (1–5) and analyzed using simple linear regression with SPSS version 27. The results indicated that all instruments were valid and reliable and satisfied the classical assumption tests. The regression analysis produced the equation Y = 3.330 + 0.935X, with a t-value of 14.557 (significance 0.000< 0.05) and an Adjusted R² of 0.793. These findings confirm that marketing strategy has a positive and significant effect on credit sales volume, accounting for 79.3% of its variation. It is concluded that strengthening marketing strategy, particularly in marketing communication and promotion, holds substantial potential to sustainably drive the growth of cooperative credit sales volume.